(untitled) (Dhaka University Journal of Science, 2018)
Phenolic compounds, known as the pyrocatechol act as a metal chelating agent. Molecular details of cross-linking of pyrocatechol by transition metal ions are largely unknown. In the present study, the molecular properties of the tris-(4´-(amino)(1,1´-biphenyl)-3,4-diol)- Fe(III) complex have been investigated using density functional theory (DFT) at 6-311G(d,p). Calculated molecular properties of the optimized structure, the binding energies and spectroscopic properties are compared with the available experimental results. For the tris-complex investigated, the binding of Fe (III) with the catechol derivative is not as strong as the binding of other metal ions with catechol. The IR stretching bands show that the strong IR intensities is due to large charge polarization. Calculated electronic band gap is 2.45 eV which is in the range of transition metal ion-tris-(4´-(amino)(1,1´-biphenyl)-3,4-diol) complexes. The metal-ligand binding energy is 513.54 kcal mol-1, which could be used in understanding the speciation of Fe(III)-catechol complex. Structural parameters obtained from the DFT calculations are in good agreement with the crystallographic data. Dhaka Univ. J. Sci. 66(1): 67-71, 2018 (January)